PENGEMBANGAN METODE PERINGATAN DINI SERANGAN NEMATODA PADA GUAVA KRISTAL: KORELASI PERFORMA TANAMAN DENGAN KERUSKAN AKAR DAN POPULASI NEMATODA - Swibawa, I Gede (Jurnal Agrotek Tropika, 2025)
Plant parasitic nematodes infestation was once a constraint for guava crystal cultivation at PT GGP Lampung. The nematode infestation not only reduced crops production but also shortened the period of guava crystal production. Routine monitoring to assess crop damage and the population of plant parasitic nematodes should avoid disrupting the root zone of guava crystal crops. The purposed of this research was to study correlation between above-ground crop performance and plant parasitic nematodes infestation status. Observation were conducted on guava crystal crops ± 4.5 years old that experienced severe infestation by plant parasitic nematodes located in block 108 D PG 2 and were scheduled for removal. The observed variables included above-ground crop performance, root damage, and plant parasitic nematode population. Crop performance was evaluated based on productive plant shoots, main trunk circumference, primary branch circumference, leaf color, and leaf indices. Root observations were performed by removing plants using heavy excavation equipment. Spearman’s correlation analyzes at α = 0.5 was applied to demonstrate correlations among variables. The results indicated that the crop performance, productive plant shoot, and primary branch circumference showed a negative correlation with root damage. Therefore, crops performance variables can be developed to indicate the plant parasitic nematodes infestation status in guava crystal cultivation. The study still needs to be extended to include observations of other relevant variable.